A comprehensive molecular survey of vector-borne blood parasites in cattle in Kyrgyzstan with a note of the first molecular detection of Anaplasma bovis and Candidatus Anaplasma Camelii - Altay, Kursat; Abdugani, Abdurasulov; Sahin, Omer Faruk; Muratova, Rakhima; Erol, Ufuk; Attokurov, Kursantbek; Risvanli, Ali (Springer, 2024)
Vector-borne pathogens continue to increase their impact on the livestock industry worldwide. To protect animals against these pathogens, it is very important to identify the species that cause the disease and understand their prevalence. This study aimed to investigate the presence and prevalence of vector-borne pathogens in apparently healthy cattle in different parts of Kyrgyzstan using molecular diagnostic techniques. For this purpose, 531 blood samples were collected from the Osh, Jalal-Abad, and Batken oblasts of Kyrgyzstan. The blood samples were investigated for vector-borne pathogens using PCR, RLB, and RFLP. Moreover, DNA sequence analyses were used to confirm the results of molecular techniques and phylogenetic analyses of these pathogens. 359 (67.61%) out of 531 samples were found to be infected with at least one pathogen, whereas 172 (32.39%) were detected to be negative. Thirteen vector-borne pathogens were detected in cattle blood samples, and the prevalence of these pathogens was as follows: Theileria orientalis (47.83%), T. annulata (25.61%), Babesia major (0.19%), B. occultans (0.38%), Anaplasma phagocytophilum-like 1 (3.20%), A. capra (3.01%), A. centrale (2.82%), A. bovis (1.13%), (A) ovis (0.19%), Candidatus Anaplasma camelii (0.94%), Trypanosoma theileri (19.21%), Mycoplasma wenyonii (6.03%), and Ca. Mycoplasma haemobos (2.64%). Among the positive samples, one pathogen was identified in 189 cattle (35.59%), and co-infections (two or more pathogens) were determined in 170 (32.01%) animals. Theileria parva, T. mutans, (B) bigemina, B. bovis, B. divergens, and A. marginale could not be detected in the study. Anaplasma bovis and Ca. Anaplasma camelii were detected for the first time in the country. This molecular survey provides important epidemiological and genetic data for the vector-borne pathogens in cattle. The results of the study showed that vector-borne pathogens have a significant spread and distribution in cattle in Kyrgyzstan.
Keywords: Vector-borne pathogens; PCR; RLB; RFLP; Cattle; Kyrgyzstan; Phylogeny